626Epidemiology of facial injuries in the context of fatal family violence in the Victorian population. (2nd September 2021) - Sarkar, Reena; Ozanne-Smith, Joan; Bassed, Richard
Abstract: Background: The oral cavity is reported to be a key focus of physical injury in family violence (FV). Our purpose is to explore the potential opportunity for dentists to assist in the prevention of serious injuries in FV. This paper aims to describe the patterns of orofacial injuries in FV homicides. Methods: All FV homicides in Victoria, Australia January 2006-December 2018, were identified amongst closed cases of assaults screened for eligible victim-offender relationships. Epidemiologic trends in FV in the Victorian population over the 12-year period were determined. Sociodemographic, interpersonal, incident and injury characteristics including ICD-10 coding were studied and compared across facial and non-facial injury FV subgroups. Results: There was a non-significant downward trend in FV homicide over the period. Of 170 adult cases, 150 were included for facial injury analysis. Of these, 117 (78%) showed orofacial injuries in the 12-year period. Two-step cluster analysis revealed blunt force and threat to breathing injury mechanisms to be significantly associated with facial FV and sharp force with nonfacial FV. Among the additional 26 child homicides, descriptive analysis elucidated patterns in 20 cases eligible for facial injury analysis. Coding limitations were found for the FV homicide cases. Conclusions: This population study reports significant involvement of the orofacial region in the FV homicide population during the 12-year study period, potentially informing dental practice and the related policy framework in Victoria and internationally. Key messages: The significant involvement of the orofacial region in FV homicides may inform optimal intervention outcomes in FV in Victoria.